'n Model vir 'n aanlyn GIS-vakwoordeboek - Theron, Lize-Mari (Lexikos, 2020)
A Model for an Online Specialized Dictionary for GIS.As part of a MA study completed at Stellenbosch University, a model for an online specialized dictionary for GIS was developed to address three problems. The first problem is the large number of specialized dictionaries created without the guidance of the theory of lexicography. A dictionary seldom reaches its potential of user-friendliness and accessibility without the guidance of theory of lexicography. One field of study that has this problem is Geographic Information Systems (GIS). Looking at online GIS dictionaries, the second problem is identified: the existing specialized dictionaries for GIS are not sufficient sources for GIS pedagogy in South Africa. The existing dictionaries are not aimed at any specific user. Beginners, semi-experts and experts are all treated the same without taking into account their individualized needs. There is also no specialized dictionary that provides an operational function — all of the dictionaries focus only on text reception. A look at the communicative function of these specialized dictionaries shows the third problem: there is no GIS dictionary that offers translation equivalents in Afrikaans (or any of the other official African languages). This article proposes a model developed with the theory of lexicography that can address the gap in GIS pedagogy in South Africa, as it is intended for beginners and has both an operational and a communicative function.Keywords: specialized dictionaries; theory of lexicography; operational function; communicative function; geographic information systems; specialized lexicography; dictionary model; gis pedagogy; online dictionaries; dictionary conceptualization plan; e-learning environments; hybrid dictionary model